2019
DOI: 10.3390/ijerph16245028
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Factors Affecting Hospital Outpatient Department Visits: Korea Health Panel Survey Data from 2009 to 2016

Abstract: This study intends to inspect the sex differences in proportion of hospital outpatient department (OPD) visits in overall outpatient (OP) visits using national panel data and to explore factors that influence the proportions by sex. This study analyzed data of the 2009–2016 Korea Health Panel Survey. Fractional logit regression was applied to analyze factors that affect proportion of hospital visits among outpatient visits. Analysis of related factors was carried out first for all analysis subjects and then by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This disparity may relate to differences in the way men and women utilize healthcare services. Although women visit the doctor more often than men (You et al, 2019), men often utilize healthcare services in a business-like manner, are more likely to want active treatment, and may be more willing to undergo a major surgery (Reid et al, 2023). This study found younger participants to be relatively more willing to receive a KT, which is consistent with the findings of previous studies (Alansari et al, 2017; Tan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This disparity may relate to differences in the way men and women utilize healthcare services. Although women visit the doctor more often than men (You et al, 2019), men often utilize healthcare services in a business-like manner, are more likely to want active treatment, and may be more willing to undergo a major surgery (Reid et al, 2023). This study found younger participants to be relatively more willing to receive a KT, which is consistent with the findings of previous studies (Alansari et al, 2017; Tan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, improving quality of care at primary and secondary care facilities may also need to be accompanied by the implementation and enforcement of an effective referral mechanism across the public healthcare network to alleviate the problem of overcrowding at higher levels of care. Similar mechanisms exist in developed nations such as Britain, France, Germany, Singapore, South Korea, etc., where deviating from predefined referral pathways may lead to penalties for non-urgent cases in terms of delayed reimbursement, higher copayment, or longer wait times (P. Jia et al 2017; You et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similar mechanisms exist in developed nations such as Britain, France, Germany, Singapore, South Korea, etc., where deviating from predefined referral pathways may lead to penalties for non-urgent cases in terms of delayed reimbursement, higher copayment, or longer wait times (P. Jia et al 2017;You et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In general, females use the health care system more than males (27)(28)(29). We found no difference between sexes in requests for HbA 1c testing, but the higher number of phone consultations in the intervention group was attributable to higher use by females.…”
Section: Discussionmentioning
confidence: 99%